Rancher, farmer, fisherman : conservation heroes of the American heartland - Horn, Miriam (W.W. Norton & Company, Inc., 2016)
Traces the conservation movement by ranchers, farmers, river workers, and fishermen who in spite of separating themselves from political environmentalism are helping to restore and protect America's grasslands, wildlife, wetlands, and oceans.